The Effects on Rabbits of Immunization with Bovine Thyroid-Stimulating Hormone and its Subunits - Beall, Gildon N. (1973)
Rabbits were immunized with bovine thyroid-stimulating hormone (bTSH), bovine Inteinizing hormone (bLH), and their subunits. In two immunization experiments, thyroid-stimulating activity was found in the serum of 6 out of 12 rabbits immunized with bTSHβ subunits. The thyroid-stimulating activity in the anti-bTSHβ sera was greater at 2 h than at 8, was eluted with the globulin fraction from Sephadex G-100, was completely neutralized by both anti-bTSH and anti-rabbit gamma globulin, and was completely suppressed by administration of triiodothyronine (T(3)) to the immunized rabbit. These findings led to the conclusion that the thyroid-stimulating activity resided in soluble complexes of rabbit TSH bound to anti-bTSHβ. Two of nine rabbits immunized with bTSH developed thyroid-stimulating activity in their serum, but it was nonsuppressible by T(3). None of the animals immunized with bTSHα, bLH, bLHβ, or bLHα developed serum thyroid-stimulating activity. Hypopituitary hypothyroidism, evidenced by decreased serum thyroxine (T(4)) and thyroidal (131)I uptake and by the histologic appearance of large follicles with flat cells, was found in the bTSHβ- and bTSH-immunized animals, despite the presence of thyroid-stimulating activity in the serum of many. The reasons for this paradox are unclear; possibly the complexes block the effect of TSH on the rabbit thyroid.